Long-term influence of tailings wastewater on mechanical performance and microstructure of dam concrete: A case study in southeastern China. (December 2021) - Meng, Tao; Lian, Songsong; Yu, Hongming; Yang, Chaojun; Wang, Menghua
Abstract: Tailings wastewater contains a large number of harmful ions which damage the hydraulic concrete structures and seriously affect the safety of water conservancy systems. This paper studied the dam concrete of a medium-sized reservoir in southeastern China which was corroded by tailings wastewater. To this end, a long-term follow-up investigation was conducted into the corrosion of the dam concrete during the period from 2013 to 2019. A multiscale analysis was also carried out on the long-term influence of the tailings wastewater on the mechanical performance and microstructure of the dam concrete. The results revealed that the corrosion by the tailings wastewater containing H + and SO 4 2 − caused a significant decline in the mechanical performance of the dam concrete in terms of the increase in the carbonation depth and the reduction of the compressive strength. Compared to the time period from 2006 to 2013, the rate of corrosion slowed down during 2013–2019. Furthermore, the main reason for the deterioration of the dam concrete was that the attack of H + and SO 4 2 − resulted in the dissolution erosion and expansion erosion of the dam concrete. The dissolution erosion of the concrete led to the increase in the average pore diameter, median pore diameter, and porosity of the dam concrete, while the expansion erosion improved the formation of gypsum and ettringite. Moreover, the dam concrete experienced various degrees of corrosion in different zones. Specifically, the dissolution erosion was most serious in the tidal zone, while the expansion erosion was severest in the submerged zone. Finally, this paper can provide a frame of reference for the research on the corrosion mechanism and service safety of hydraulic concrete structures eroded by various types of tailings wastewater.